Awareness Regarding Family Planning Methods Among Final Year Medical Students - Nadia Somroo; Syed Muhammad Zulfiqar Hyder Naqvi; Syed Imtiaz Ahmed Jafry; Paras Saleem; Nazia Jameel; Mudassir Hussain (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
A cross-sectional awareness survey was conducted among final year MBBS students of ISRA University, Hyderabad from May 2017 to November 2017. After checking eligibility and taking verbal informed consent, 100 participants were included in the study and interviewed using a self-administered questionnaire. Data was analyzed on Statistical Package for Social Sciences version 21. The study results showed that 29 (29%) of the study participants got information about family planning methods from health care providers, 27 (27%) through social circle, 24 (24%) through mediawhile 20 (20%) through conference, meetings and events. Furthermore, 42 (42%) of the participants correctly identified all permanent family planning methods, 65 (65%) correctly identified temporary family planning methods, 47 (47%) correctly identified short-term family planning methods whereas 54 (54%) correctly identified long term family planning methods. Efforts by both public and private sector to enhance awareness regarding family planning methods among medical students are recommended